Doublages, langues et voix en Europe - Michel Chion (Mise au Point)
Trying to assess the development of dubbing is extremely difficult as it would require an enormous amount of listening and investigation... Michel Chion gives us examples taken from different films which are franco-italian co-productions. He also talks about the importance of exchanging actors from one country to another. Questions such as those concerning accents and the significance of the nuances of these implied in the meaning of a film are also raised. Dubbing, however, is not an ideal solution nor are sub-titles. But dubbing can have a certain charm even if some people think that old-style dubbing is out dated. Dubbing is subjected to a matter of agreements as are the social connotations linked to accents. Many people in a film audience would have to be questioned in order to study how films which are either dubbed or sub-titled are received. Michel Chion cites Scarface by Brain De Palma as an example of dubbing which has become extremely popular.